Perancangan Aplikasi Layanan Jasa Perbaikan Komputer dan Laptop Toshiba Berbasis Android - Muh Dimas Galuh Nugraha; Linda Atika (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In improving customer service and guaranteeing customers who use the Toshiba brand, Toshiba is still opening Authorized Service Partnerships in various regions, one of which is the ASP Toshiba Palembang which provides laptop and computer repair services, as well as pick-up services. Improving services can affect the results achieved. Based on this, it is necessary to take action by creating an Android-based computer and laptop repair service application that will facilitate the ordering process for customers by having the ability to pick up goods and view order status. The result that can be felt by ASP Toshiba Palembang is that it can store data. The system is built using the Java programming language for Android-based mobile managers and messengers, while the admin uses a website based on the PHP programming language, MySQL as a database and Firebase for push notifications. The system development methodology used is an iterative model. The results of this study are to produce an Android-based PC and laptop repair service application that allows the application to improve customer service for ASP Toshiba Palembang, by providing convenience benefits for cutomers in placing orders and ASP Tohiba Palembang can perform transaction data recording of laptop and computer repair orders.